Epidemic outbreak of apple blotch disease: epidemiology and management in Himachal Pradesh - NIRUPMA SHARMA, V.S. THAKUR* (Indian Phytopathology, 2010)
Apple blotch complex caused by Marssonina and Alternaria sp. is an important disease manifested recently in all apple growing states of India. The disease appears in the form of dark brown blotch on the upper side of the leaf in the second week of June under humid weather conditions. The correlation analysis revealed that the prevalence of blotch disease was based on the physio-epidemiological conditions wherein leaf ageing followed by average temperature above 200C and 70 per cent relative humidity atleast continuously for 5-6 days, induce yellowing and defoliation process. The disease management with fungicide tested as preventive sprays against premature leaf fall of apple, Indofil M-45 (0.3%), Antracol (0.3%), Indofil Z- 78 (0.3%), Bavistin (0.05%), Kocide (0.3%), Tohfa (0.075%) and Copter (0.3%) provided hundred percent disease control with very good to excellent fruit finish.